Razvoj metode semantičnih polj ob primeru hebrejskega pojma resnice - Avsenik Nabergoj, Irena (Bogoslovni vestnik, 2023)
The aim of the article is to show the advantages of the method of analysis of lexical and semantic fields in the field of literature while showing the polysemy of the vocabulary that expresses the semantic aspects of the concept of truth in the Bible. Semantic field analysis considers basic linguistic, literary, and rhetorical structures from the smallest units, such as a line, to larger fragments of various types and genres of texts. Special attention is paid to the constant connections between synonyms and antonyms in the typical biblical parallelismus membrorum and in other basic literary forms. The starting point of any analysis is the consideration of the relationship between synonyms and antonyms with a similar meaning. Literary structures of semantic fields that express the dimensions of the concept of “truth” in the Hebrew Bible include synonyms and antonyms of the root 'mn. The root 'mn is mostly used in the sense of “firmness, steadfastness, trustworthiness, constancy, duration, faithfulness, truth” in relation to God and humanity. From the basic meaning of the root 'mn comes the meaning of faith as trust in someone whom a person considers reliable, trustworthy. In order to understand the entire semantic scope of the concept of truth, in the analysis of the original text we also take into account the use of vocabulary in the most influential translations of the Bible, such as the Septuagint and the Vulgate, in current everyday use and in the development of theological vocabulary in the field of philosophy and theology. The traditional understanding of the term “truth” in everyday speech is focused on conformity with some fact or with the external circumstances of a certain reality and on the evidence of “fairness” in relations between people. The analysis of semantic fields finally helps us to determine what are the specific aspects of the biblical concept of truth compared to ancient and modern secular literature.
Keywords: bralna izkušnja; multiple meanings of words; reading experience; semantic fields of truth; semantična polja resnice; sinonimi in antonimi; structural linguistics; strukturalno jezikoslovje; synonyms and antonyms; the role of parallelismus membrorum; večpomenskost besed; vloga slovničnega paralelizma (parallelismus membrorum)